Physical, physicochemical and taxonomic characterization of Psidium araça Raddi - Padilha, Maria do Rosário Fátima; Shinohara, Neide Kazue Sakugawa; Pereira, Emanuella de Paula Rodrigues; Pimentel, Rejane Magalhães Mendonça; Andrade, Samara Alvachian Cardoso; Portela, Fábio Henrique; Bernardino, Allan Victor Souza (Journal of Environmental Analysis and Progress, 2016)
New research has stimulated a large reevaluation of species with regards to the use of fruits from native plants. Araçá (a small Brazilian guava-like fruit) is found scattered in the wild in Pernambuco/Brazil. There is a scarcity of detailed studies on such regional fruit trees, especially the Psidium araçá Raddi species, whereas there is an enormous possibility to explore the potential offered by these fruits, such as in the field of gastronomy, where the search for new ingredients and exotic flavors associated with functional properties has been increasing. This article aimed to evaluate the physical, physicochemical and taxonomic characterization of araçá obtained from different agricultural regions of Pernambuco in order to investigate the possibility of developing new products from this native fruit. The taxonomic identification confirmed that all collected material belonged to the species P. araçá Raddi. An average weight of 7.45 g/fruit was observed. With respect to pH, values between 3.17 and 3.48 were found, and the acidity as a percentage of citric acid was on the order of 0.96% to 0.99%. It was shown that the P. araçá Raddi fruit has a desirable quality for the food industry, presenting excellent conditions for the development of formulations of high commercial value and promising application in the national gastronomy.